SYBR GREEN BASED DUPLEX RT-qPCR DETECTION OF A BEGOMOVIRUS, TOMATO LEAF CURL NEW DELHI VIRUS-[POTATO] ALONG WITH POTATO VIRUS X AND POTATO LEAFROLL VIRUS IN POTATO - A, Jeevalatha; Kaundal, P; Kumar, Ashwani; Guleria, Anupama; S, Sundaresha; Pant, R P; Sridhar, J; Venkateswarlu, V; Singh, B P (Potato Journal, 2017)
SYBR green based RT-qPCR assay coupled with melting curve analysis was developed for the detection of Tomato leaf curl New Delhi virus-potato (ToLCNDV-[potato]), Potato virus X (PVX), and Potato leafroll virus (PLRV). The assays were standardized using four sets of primers for each target and selecting best primer set, optimizing primer concentration and cycle conditions. The amplification of products were verified by specific melting peaks for each targets viz., ToLCNDV-[potato], PLRV, PVX and ef-1 Î± gene of potato. Then, duplex RT-qPCR assays were developed to detect these viruses along with elongation factor 1-Î± (ef-1 Î±) gene as plant internal control and to detect ToLCNDV-[potato] along with PVX and PLRV. In duplex RT-qPCR assay, a melting peak specific to ToLCNDV-[potato] was observed along with melting peak of other virus/ ef-1 Î± gene. The assays could detect up to 20 copies/Î¼l using serially diluted plasmids harbouring the targets and up to 0.025 fg of total RNA from infected plant tissues. Sensitivity of duplex RT-qPCR assay was comparable to singleplex RT-qPCR assays. The developed assays could consistently detect these viruses in field samples and was more sensitive than conventional RT-PCR.